2018
DOI: 10.1097/md.0000000000011547
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of fluvoxamine in adults with social anxiety disorder

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Nevertheless, this review included rankings of medications which are missing in previous published NMAs and includes the gradings of RCTs by medication class which is a novel method of interest by the GRADE Working Group. The data included in this review are also consistent with findings from other systematic reviews and meta-analyses in identifying that SSRIs like paroxetine are first-line agents for the treatment of SAD (Ballenger et al, 1998;Bandelow et al, 2002;Bandelow et al, 2012;Bandelow & Michaelis, 2015;Blanco et al, 2003;Van der Linden et al, 2000), aside from documented differences in the incidence of specific adverse events, existing evidence for a NMA does not suggest differences in the effectiveness of this drug(s) (Blanco et al, 2003;Hansen et al, 2008;Liu et al, 2018;Mayo-Wilson et al, 2014). The outcomes of this review are also generalisable to a diverse range of settings, and the interventions targeted both men and women across a wide age range.…”
Section: Discussionsupporting
confidence: 78%
“…Nevertheless, this review included rankings of medications which are missing in previous published NMAs and includes the gradings of RCTs by medication class which is a novel method of interest by the GRADE Working Group. The data included in this review are also consistent with findings from other systematic reviews and meta-analyses in identifying that SSRIs like paroxetine are first-line agents for the treatment of SAD (Ballenger et al, 1998;Bandelow et al, 2002;Bandelow et al, 2012;Bandelow & Michaelis, 2015;Blanco et al, 2003;Van der Linden et al, 2000), aside from documented differences in the incidence of specific adverse events, existing evidence for a NMA does not suggest differences in the effectiveness of this drug(s) (Blanco et al, 2003;Hansen et al, 2008;Liu et al, 2018;Mayo-Wilson et al, 2014). The outcomes of this review are also generalisable to a diverse range of settings, and the interventions targeted both men and women across a wide age range.…”
Section: Discussionsupporting
confidence: 78%
“…One hundred and two meta‐analyses fulfilled the inclusion criteria (see Figure 1 and supplementary information). These encompassed 69 meta‐analytic comparisons of pharmacotherapies with placebo or TAU, 26 comparisons of psychotherapies with placebo or TAU, 11 comparisons of psychotherapies vs. pharmacotherapies head‐to‐head, and 13 comparisons of combined psychotherapy and pharmacotherapy to either monotherapy 6,12,13,34‐134 . The 102 meta‐analyses encompassed 3,782 RCTs (range: 2 to 522) and 650,514 patients (range: 65 to 116,477) (see supplementary information).…”
Section: Resultsmentioning
confidence: 99%
“…In the largest meta-analyses for anxiety disorders, pharmacotherapies achieved SMDs in comparison to placebo between 0.33 and 0.45 53,56,64 (see Figure 2). Overall, effect sizes for pharmacotherapy were between 0.01 and 0.56, with the majority of effect sizes being small 53,[55][56][57][58][59][60][61][62][63][64]66,67,69,70 (see supplementary information). RR ranged between 1.20 and 4.03, with most values being small, one medium (monoamine oxidase inhibitors), and one large (benzodiazepines, RR=4.03) 69 .…”
Section: Anxiety Disordersmentioning
confidence: 99%
“…Paroxetine is a drug indicated for the treatment of variety of anxiety disorders, including generalized anxiety disorder (GAD, ICD-10-CM code: F41.1 [ 17 ]), obsessive–compulsive disorder (OCD, ICD-10-CM code: F42.3, F42.2, F42.9, F42.8 [ 18 ]), major depressive disorder (MDD, ICD-10-CM code: F32, F33 [ 19 ]), premenstrual dysphoric disorder (PDD, ICD-10-CM code: F32.81 [ 20 ]), post-traumatic stress disorder (PTSD, ICD-10-CM code:F43.1 [ 21 ]), panic disorder (PD, ICD-10-CM code: F41.0 [ 22 ]), social anxiety disorder (SAD, ICD-10-CM code: F40.1, F40.10, F40.11 [ 5 ]) and vasomotor symptoms [ 23 , 24 , 25 , 26 ]. It is worth emphasizing that in the treatment of PTSD there are only two approved pharmacotherapies based on SSRIs, including Paxil (paroxetine hydrochloride).…”
Section: Paroxetine—general Information and Historymentioning
confidence: 99%
“…[ 47 ]. In addition to hydrochloride, paroxetine mesylate is also available [ 23 ]. It can be concluded that nowadays, the structure of paroxetine is well-researched and understood ( Figure 1 ).…”
Section: Paroxetine—chemistrymentioning
confidence: 99%